The Mechanism Technological Developments in The Contemporary Cinematic Film Scenario (Al-Academy, 2025)
This research deals with the mechanisms of adapting technological development in writing the scripts of contemporary films and series, away from cinematic and television scripts that focus on recurring dramatic themes steeped in social issues such as love and treachery. Technological development in recent times has brought about a radical transformation in various aspects of life. Including the film and television industry, this development has greatly influenced how film and television scenarios are written, as it has created new tools and methods that were not previously available. The emergence of new technology, such as virtual and augmented reality technology, 3D graphics, and motion capture technology. All of these innovations have made screenwriters take a new approach and unleash their imaginations by writing more innovative scripts It is more dynamic than imagining imaginative virtual worlds, creating strange virtual characters, and dealing with technology topics as a fact and not as a fantasy, and with modern narrative patterns. Using some of the films mentioned in the body of the research, the researchers reviewed these developments and the mechanisms for employing them in contemporary scenarios, followed by an analysis of the research sample. The researchers conclude the research by drawing a number of results and conclusions and presenting recommendations and proposals.